The league. The complete season 1 [videorecording (DVD)] - Schaffer, Jeff; Marcus Schaffer, Jackie (2010)
A full-contact look at the hyper-competitive, hysterically unrestrained world of fantasy football! The League's members are a tight crew of long-time buddies, but that doesn't stop an all-out blitz of trash-talking, deceit, and ruthless extortion. Watch as their obsession with winning the highly coveted yet utterly absurd championship trophy impacts their careers, sex lives, families, and, above all, their dignity.